DINAMIKA IMPLEMENTASI GOOD UNIVERSITY GOVERNANCE PADA PERGURUAN TINGGI PESANTREN - Rafik, Ainur; Irawan, Bambang (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2024)
Implementing Good University Governance (GUG) in Islamic Private Higher Education Institutions (PTKIS) based in pesantren presents unique dynamics compared to conventional universities. As institutions that integrate pesantren traditions with modern higher education systems, PTKIS pesantren face the dual challenge of preserving their moral-spiritual identity while simultaneously meeting global governance standards emphasizing accountability, transparency, and efficiency. This study employs library research to identify practices, challenges, and opportunities for applying GUG within the context of pesantren. The findings highlight the emergence of a moral governance concept as an additional pillar of GUG in PTKIS pesantren. This pillar emphasizes ta’dib (character education), sharia-based transparency, and sincerity (ikhlas), embedding a spiritual dimension into governance practices. Through this approach, PTKIS pesantren can construct a governance model that is both accountable and deeply rooted in Islamic values. In doing so, they contribute to strengthening the discourse on higher education governance in Indonesia and offering an alternative model that harmonizes managerial professionalism with moral-spiritual foundations.